Comparison of long term outcome in patients with or without aortic ring abscess treated surgically for aortic valve infective endocarditis. Issue 2 (1st February 1999) - Danchin, N; Retournay, G; Stchepinsky, O; Selton-Suty, C; Voiriot, P; Hoen, B; Canton, P; Villemot, J-P; Mathieu, P; Cherrier, F
Abstract : Objective: To assess the long term prognostic significance of aortic valve ring abscess in patients with aortic endocarditis. Patients: A consecutive series of 75 patients who had surgery for aortic infective endocarditis between 1981 and 1989; 35 had aortic ring abscesses (group 1) and 40 did not (group 2). Mean age did not differ between the two groups. Prosthetic valve endocarditis was present in 17% of group 1 and 5% of group 2. Pneumococcal or β haemolytic streptococcal endocarditis was more common in patients with native valve endocarditis who had aortic ring abscesses (20% v 5%). Design: Cohort analysis. Results: In-hospital mortality (11.4% v 7.5%) and 10 year survival (56% v 66%) were not significantly different between groups 1 and 2. In patients with native valve endocarditis, 10 year survival was 62% and 66%, respectively for patients with or without ring abscess, and 10 year reintervention-free survival was 38% v 58% (p = 0.11). In these patients, the presence of an intercurrent illness, severe congestive heart failure before surgery, and use of valved conduits for surgical treatment were predictors of poorer long term survival. At follow up residual aortic regurgitation was documented in 72% of patients in group 1 and 26% in group 2 (p < 0.01). Conclusions: Aortic valve ring abscess is not an independent marker of poor long term outcome in patients with infective endocarditis. However, as residual aortic regurgitation appears frequent at follow up, specific surgical techniques should be considered in patients with paravalvar abscesses.